2013
DOI: 10.1089/jmf.2012.2617
|View full text |Cite
|
Sign up to set email alerts
|

Moscatilin Induces Apoptosis and Mitotic Catastrophe in Human Esophageal Cancer Cells

Abstract: Moscatilin, a bibenzyl derivative from the orchid Dendrobium loddigesii, has been shown to possess anticancer activity. We examined the effect of moscatilin on human esophageal cancer cells, including squamous cell carcinoma (SCC) and adenocarcinoma (ADC) cells and its possible mechanisms. Moscatilin suppressed the growth of both the histological cell lines in a dose- and time-dependent manner. Morphological changes indicative of apoptosis and mitotic catastrophe were observed following moscatilin treatment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 30 publications
(33 reference statements)
4
23
0
Order By: Relevance
“…Furthermore, moscatilin was revealed to strongly suppress pancreatic tumor growth and development, without any apparent toxicity, in vivo . In previous studies, moscatilin has been demonstrated to possess proapoptotic effects in esophageal cancer, antimetastatic effects in lung and breast cancer, and anti-angiogenic activity against malignant tumors (1619). These previous data indicated that moscatilin is worthy of being developed into a therapeutic agent for the prevention and treatment of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, moscatilin was revealed to strongly suppress pancreatic tumor growth and development, without any apparent toxicity, in vivo . In previous studies, moscatilin has been demonstrated to possess proapoptotic effects in esophageal cancer, antimetastatic effects in lung and breast cancer, and anti-angiogenic activity against malignant tumors (1619). These previous data indicated that moscatilin is worthy of being developed into a therapeutic agent for the prevention and treatment of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…denneanum , was revealed to exert proapoptotic effects in pancreatic cancer cells. Moscatilin has been reported to exert proapoptotic effects in esophageal cancer, antimetastatic effects in lung and breast cancer, and anti-angiogenic activities against malignant tumors (1619). The present study aimed to investigate whether the cytotoxicity of moscatilin on Panc-1 cells was associated with intracellular ROS production, and to determine the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, 40 can be considered as a compound with a broad potential against esophageal cancer. [76] Recently, Yang et al reported the isolation and structural characterization of two dihydrostilbenoid derivatives, namely dendrocandins T (41), U (42), and B (43), together with other dihydrostilbenoids that displayed significant effects in the neurite outgrowthpromoting activity assay. [77] Gigantol (44) suppressed the migratory behavior of non-small cell lung cancer cells (NSCLC) H460 and H292 but did not show a similar effect on HaCat normal human keratocytes.…”
Section: Dihydrostilbenoids and Related Derivativesmentioning
confidence: 99%
“…Immunofluorescence studies revealed multipolar mitosis and multinucleation in cells, suggesting the development of mitotic catastrophe. Thus, 40 can be considered as a compound with a broad potential against esophageal cancer …”
Section: Introductionmentioning
confidence: 99%
“…The cells exit mitosis without cell division, forming a single giant cell with multi-nuclei and decondensed chromatin [27]. Moscatilin also produces the aforementioned changes in vitro [31]. This type of cell death could result from the alteration in the regulators of mitosis, including cell-cycle-specific kinases (e.g.…”
Section: Discussionmentioning
confidence: 99%